Integrasi Sistem Verifikator DPT Pemilihan Kepala Desa Berbasis Quick Response Code - Akmad Rizal Zulmi; Yusron Rijal (SMATIKA JURNAL : STIKI Informatika Jurnal, 2020)
The village head election is an example of a general election that requires the role and active participation of the community. In the election of village heads it is usually done at the village hall at one time. Because it is only done in one place and a large number of voters in one village causes a long queue registration. In registration, the Voter List remains a very important data as a basis for political participation for the selection of systems needed to support and verify the DPT as an administrative process before voting. another system is the village head's voting system based on patterns. The object of research used was DPT data obtained from the Chair of the Committee. This DPT verification system provides benefits in the DPT data verification process which quickly and precisely improves the voting process and also avoids multiple elections in the voting process. The integration of the DPT verifier system for village head election based on the quick response code has been approved using Black Box Testing and has run well with 100% accuracy.